Mortality in British military participants in human experimental research into chemical warfare agents at Porton Down: cohort study. (24th March 2009) - Venables, K M; Brooks, C; Linsell, L; Keegan, T J; Langdon, T; Fletcher, T; Nieuwenhuijsen, M J; Maconochie, N E S; Doyle, P; Beral, V; Carpenter, L M
Abstract : Objective To investigate any long term effects on mortality in participants in experimental research related to chemical warfare agents from 1941 to 1989. Design Historical cohort study. Data sources Archive of UK government research facility at Porton Down, UK military personnel records, and national death and cancer records. Participants 18 276 male members of the UK armed forces who had spent one or more short periods (median 4 days between first and last test) at Porton Down and a comparison group of 17 600 non-Porton Down veterans followed to 31 December 2004. Main outcome measures Mortality rate ratio of Porton Down compared with non-Porton Down veterans and standardised mortality ratio of each veteran group compared with the general population. Both ratios adjusted for age group and calendar period. Results Porton Down veterans were similar to non-Porton Down veterans in year of enlistment (median 1951) but had longer military service (median 6.2 v 5.0 years). After a median follow-up of 43 years, 40% (7306) of Porton Down and 39% (6900) of non-Porton Down veterans had died. All cause mortality was slightly greater in Porton Down veterans (rate ratio 1.06, 95% confidence interval 1.03 to 1.10, P<0.001), more so for deaths outside the UK (1.26, 1.09 to 1.46). Of 12 cause specific groups examined, rate ratios in Porton Down veterans were increased for deaths attributed to infectious and parasitic (1.57, 1.07 to 2.29), genitourinary (1.46, 1.04 to 2.04), circulatory (1.07, 1.01 to 1.12), and external (non-medical) (1.17, 1.00 to 1.37) causes and decreased for deaths attributed to in situ, benign, and unspecified neoplasms (0.60, 0.37 to 0.99). There was no clear relation between type of chemical exposure and cause specific mortality. The mortality in both groups of veterans was lower than that in the general population (standardised mortality ratio 0.88, 0.85 to 0.90; 0.82, 0.80 to 0.84). Conclusions Mortality was slightly higher in Porton Down than non-Porton Down veterans. With lack of information on other important factors, such as smoking or service overseas, it is not possible to attribute the small excess mortality to chemical exposures at Porton Down.